Heterolytic Cleavage of Dihydrogen by an Iron(II) PNP Pincer Complex via Metal-Ligand Cooperation - Bichler, Bernhard (Organometallics, 2013)
The bis-carbonyl Fe(II) complex trans-[Fe(PNP-iPr)(CO)2Cl]+ reacts with Zn as reducing agent under a dihydrogen atmosphere to give the Fe(II) hydride complex cis-[Fe(PNP-iPr)(CO)2H]+ in 97% isolated yield. A crucial step in this reaction seems to be the reduction of the acidic NH protons of the PNP-iPr ligand to afford H2 and the coordinatively unsaturated intermediate [Fe(PNPH-iPr)(CO)2]+ bearing a dearomatized pyridine moiety. This species is able to bind and heterolytically cleave H2 to give cis-[Fe(PNP-iPr)(CO)2H]+. The mechanism of this reaction has been studied by DFT calculations. The proposed mechanism was supported by deuterium labeling experiments using D2 and the N-deuterated isotopologue of trans-[Fe(PNP-iPr)(CO)2Cl]+. While in the first case deuterium was partially incorporated into both N and Fe sites, in the latter case no reaction took place. In addition, the N-methylated complex trans-[Fe(PNPMe-iPr)(CO)2Cl]+ was prepared, showing no reactions with Zn and H2 under the same reaction conditions. An alternative synthesis of cis-[Fe(PNP-iPr)(CO)2H]+ was developed utilizing the Fe(0) complex [Fe(PNP-iPr)(CO)2]. This compound is obtained in high yield by treatment of either trans-[Fe(PNP-iPr)(CO)2Cl]+ or [Fe(PNP-iPr)Cl2] with an excess of NaHg or a stoichiometric amount of KC8 in the presence of carbon monoxide. Protonation of [Fe(PNP-iPr)(CO)2] with HBF4 gave the hydride complex cis-[Fe(PNP-iPr)(CO)2H]+. X-ray structures of both cis-[Fe(PNP-iPr)(CO)2H]+ and [Fe(PNP-iPr)(CO)2] are presented